2020
DOI: 10.1002/jsfa.10773
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high‐pressure processing on reducing the glycaemic index of atemoya puree

Abstract: BACKGROUND This study investigated the effects of high‐pressure processing (HPP) on the glycaemic index (GI) of atemoya puree (AP) in rats. Sprague–Dawley rats were fed with unprocessed and high‐pressure processed atemoya puree (HPP‐AP), and the GIs for the unprocessed AP and HPP‐AP were calculated from changes in blood glucose concentrations within 2 h after meals. The physicochemical properties of AP were analysed to understand the mechanism affecting its GI. RESULTS The results showed that HPP (600 MPa for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Although HPP treatment did not change the composition of monosaccharides, it significantly reduced the SDF, delayed the release of glucose, slowed the increase in postprandial blood glucose levels, delayed the peak time of glucose response (T max ), and reduced the GI in rats. 16 Li et al 17 also revealed that the damage to SI activity in mangoes increased with increase in the processing pressure; additionally, the degree of damage to the enzyme activity was proportional to the increase in temperature. SI exhibited better tolerance to pressure in a lower pH environment.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although HPP treatment did not change the composition of monosaccharides, it significantly reduced the SDF, delayed the release of glucose, slowed the increase in postprandial blood glucose levels, delayed the peak time of glucose response (T max ), and reduced the GI in rats. 16 Li et al 17 also revealed that the damage to SI activity in mangoes increased with increase in the processing pressure; additionally, the degree of damage to the enzyme activity was proportional to the increase in temperature. SI exhibited better tolerance to pressure in a lower pH environment.…”
Section: Discussionmentioning
confidence: 96%
“…The increase in processing pressure also led to a more pronounced increase in the dietary fibre content, and concurrently, the enzyme activities of SI, PME, and PG in the atemoya puree were reduced, and the damage to the enzyme activity increased with increase in pressure. Although HPP treatment did not change the composition of monosaccharides, it significantly reduced the SDF, delayed the release of glucose, slowed the increase in postprandial blood glucose levels, delayed the peak time of glucose response ( T max ), and reduced the GI in rats 16 . Li et al 17 .…”
Section: Discussionmentioning
confidence: 99%